ANALISIS PERAN PENDETA DALAM MENINGKATKAN KUALITAS DAN PEMBERDAYAAN EKONOMI BAGI JEMAAT MASA KINI - Eva Borong; Vikarya, Adrian Valarius T., Egha, Gelby Eunike Parabang (ADISAM PUBLISHER, 2025)
This research aims to analyze the role of pastors in improving the quality and economic empowerment of the congregation in today's era. Pastors, as spiritual leaders, not only focus on spiritual aspects but also have the responsibility to empower the congregation in the economic field. This study uses a qualitative approach with a case study method, involving closed observations with pastors, church leaders, and members of the congregation engaged in economic empowerment programs. Additionally, this study also observes economic programs initiated by the church, such as skills training, cooperative management, and community-based entrepreneurship. The findings of this study show that pastors play a crucial role in motivating the congregation to work hard, manage finances wisely, and create business opportunities. Through training, mentoring, and facilitation, pastors have successfully empowered the congregation to improve their economic well-being. Moreover, pastors also act as mediators between the congregation and external resources that can support economic empowerment. This study concludes that economic empowerment by pastors not only improves the material well-being of the congregation but also strengthens solidarity and commitment among church members in facing socio-economic challenges